FRAZEOLOGIK BIRLIKLARNING LINGVOMADANIY JIHATLARI - Jurayeva I.A.; Abduvaxobova M. V. (Western European Studies, 2025)
This article discusses the problems that many linguists face when translating English phraseological units (phrases, proverbs, idioms) into Uzbek, and their solutions. In addition, the origins of one of the new areas in linguistics —linguocultural studies — and its important role in translating phraseological units are analyzed
Keywords: Linguoculturology; phraseology